Simulation Model Queuing On Terminal Block M TransJakarta Busway Using PHP - Afief Alauzi (Jurnal Sistem Informasi, 2010)
This thesis, discusses queuing theory widely applied in business, industry,transportation and daily activities of another. A queue can occur if the arrivalrate greater than the level of service. In theory there are two queue model queueis a queue model of single-channel and multi-channel queuing model. First thesingle-channel queuing model there is only one service facilities, while inmulti-channel queue more than one service facility.In this thesis, the author will try to provide solutions to these problems byapplying both models to the case of the model queue in Terminal Block MTransJakarta Busway to determine the operating characteristics of queuingmodels are made using simulation techniques or formulas queue. Where is thesolution obtained will be compared to determine the level of service efficiency.In this study we concluded that the operating characteristics completion queuemodel using multi-channel model with simulation techniques is morecomplicated but more efficient.